(untitled) (TAJ: Journal of Teachers Association, 2009)
Effect of fenugreek (Trigonella foenumgraecum) on thymic volume was studied in 30 long Evans rats. Among the total, 10 were treated with only vehicle (non-diabetic control - group A); 10 were treated with streptozotocin only (diabetic control - group B) and 10 were treated with fenugreek (fenugreek treated - group C). Mean relative thymic volumes were 0.22210.018 ml/100 gm of corresponding final body weight (Mean 1 SEM), 0.14710.015 and 0.19910.020 in group A, B and C respectively. In non-diabetic control group the thymic volume was significantly higher (p=0.005) than that of diabetic control group. In fenugreek treated diabetic group the volume was also significantly higher (p=0.05) from that of diabetic control group and very much nearer to nondiabetic control group (p=0.398). Fenugreek may preserve the thymic volume considerably in diabetic rats. doi: 10.3329/taj.v16i1.3892 TAJ June 2003; Vol.16(1): 1-4